ANALISIS KINERJA PELABUHAN DAN PERSYARATAN LAPANGAN PENUMPUKAN PELABUHAN KELAS III PARIGI - Ummu Kalsum (Paser Institute Management and Busines, 2024)
Ports as transportation infrastructure that supports the smooth running of the maritime transportation system have functions that are closely related to social and economic factors. Economically, ports function as one of the driving forces of production, while socially, ports become public facilities where interactions between users (society) take place, including interactions that occur due to economic activities. This research aims to analyze the performance of the dock and the needs of the Class III Parigi Port stacking yard. This type of research uses a qualitative research approach. The research results show that the level of utilization of the Class III Parigi Port Pier is based on the BOR value resulting from two reviews, namely the BOR of the new pier and the old pier. The utilization rate of the new pier in 2022 is 17% and the BOR value in 2023 is 4%. Meanwhile, the utilization rate of the old pier in 2022 is 4% and the BOR value in 2023 is 5%. The required area for the piling field in 2022 if YOR 40% is known is 22,090 m2, when YOR 50% is known it is 17,667 m2, when YOR 60% is known it is 14,171 m2, and when YOR 70% is known it is 12,629 m2. Meanwhile, the area requirement for the piling yard in 2023 if YOR 40% is known is 10,699 m2, when YOR 50% is known it is 8,554 m2, when YOR 60% is known it is 7,128 m2, and when YOR 70% is known it is 6,106 m2.